Effect of Methyl-β-Cyclodextrin and Trehalose on the Freeze-Drying and Spray-Drying of Sericin for Cosmetic Purposes - Lorella Giovannelli; Andrea Milanesi; Elena Ugazio; Letizia Fracchia; Lorena Segale (MDPI AG, 2021)
Sericin is a protein extracted from Bombyx mori silk cocoons. Over the last decade, this wastewater product of the textile industry has shown many interesting biological properties. This protein is widely used in the cosmetic and biomedical fields. In this study, sericin has been obtained via a High-Temperature High-Pressure degumming process, and was dried using the freeze-drying (fd) and spray-drying (sd) techniques. Proteins tend to collapse during drying, hence, sericin has been dried in the presence of two selected carrier agents: methyl-β-cyclodextrin and trehalose. The obtained powders have been analyzed using thermal investigation, microscopy (optical, SEM), and granulometric and spectroscopic analyses. Moreover, the percentage yield of the spray-drying process has been calculated. Both the agents were able to significantly improve the drying process, without altering the physico-chemical properties of the protein. In particular, the co-spray-drying of sericin with methyl-β-cyclodextrin and trehalose gave good process yields and furnished a powder with low moisture content and handling properties that are better than those of the other studied dried products. These characteristics seem to be appropriate and fruitful for the manufacturing of cosmetic raw materials.